Pendampingan Pembiasaan Salat Duha Bersama untuk Menanamkan Nilai-Nilai Keagamaan Islam pada Anak Usia Dini - HARIANTO, JIMI (Karsa Bhakti : Journal of Community Service, 2026)
Introducing Islamic religious values from an early age is a crucial foundation in shaping a child's character. However, field challenges often lie in delivery methods that lack aspects of habit formation and direct role modeling. This community service activity aims to implement the habituation method of congregational Dhuha prayer as an effective means of introducing basic Islamic values to students at PAUD KB Nusa Indah, Sukamulya, Lampung. The research method used is action research with a participatory qualitative approach, integrated into the service program. The activity was carried out in two cycles, covering four stages: (1) planning, (2) action implementation (Dhuha prayer habituation), (3) observation/monitoring, and (4) reflection. The subjects of the activity were 15 children aged 4-6 years and 3 educators. Data collection techniques included participant observation, in-depth interviews with educators, and documentation. The implementation results show that the consistent habituation of congregational Dhuha prayer successfully increased children's understanding of ablution procedures (wudlu), the sequence of prayer movements, and memorization of short prayers, and instilled values of discipline, orderliness, and togetherness. The role of educators as exemplary models (uswah hasanah) and enjoyable facilitators was key to the success of the internalization process. It can be concluded that the habituation method through the habit of congregational Dhuha prayer is an effective and contextually appropriate strategy for introducing Islamic values in early childhood at PAUD KB Nusa Indah. The recommendation for the institution is to make this activity a structured routine and involve parents to sustain it in the family environment.